If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4 + 4x = 16 Reorder the terms: 4 + 2x + 4x = 16 Combine like terms: 2x + 4x = 6x 4 + 6x = 16 Solving 4 + 6x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 6x = 16 + -4 Combine like terms: 4 + -4 = 0 0 + 6x = 16 + -4 6x = 16 + -4 Combine like terms: 16 + -4 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 27+4b=5+6(5b-5) | | 27+4b=5+6(5b-5)answer | | 3.14d=298.2 | | -10n-15=-6n+17 | | 3x^2+12x+40=0 | | (x^2-4x)(x^2+4x)=x^2-4x+20 | | -3y=-9-6x | | 4(-5h-2)=-68 | | -3x+4x-3=5 | | a(x-b)-b(x+a)=0 | | (m-1)x^2-2x+1-m=0 | | 36=x-3 | | -21+6(x+3)=33 | | C^2+7c-18= | | (5-15y)-(12+16y)= | | -5u+41=6(u+5) | | 9=9x-124 | | (x-3)*(x^2-6x)=7 | | wy+5y=T | | 4x+16w+64= | | x+4x=33045 | | X^2+5*x+34=0 | | 6x-4x=6x-8x+2 | | -4-6(6m-2)=-64 | | 2.39=m(3.29)+0.59 | | -2x-8x=4-8x | | 5x-(8-x)=4a-10 | | 5p-2p=54 | | 1.3x-4.42=x-2.5 | | 4w+2w=48 | | (-1.59)(-0.5)= | | 240=lwh |